Potensi perasan Daun Binahong (Anredera cordifolia) sebagai antibakterial pada kultur media bakteri Staphylococcus aureus dan Esherichia coli penyebab mastitis klinis penyebab mastitis Sapi Perah (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2017)
This research was conducted to determine the ability of binahong (Anrederacordifolia (Ten.) Steenis) leaf juice as alternative herbal antibacterialagainst teat dipping mastitis of livestock. Pure isolate of Staphylococcusaureus and Esherichia coli taken from sub clinical mastitis of dairy cowwere used in this experiment. The experiment was examined with four differenttreatments and five replication 60% (P 1 ), 80% (P 2 ), and 100% (P 3 ) ofbinahong leaf juice concentration’s as treatment and iodips 10% (P0) as placebo.Based on statisctical method, the result prove that binahong’s leaf juice hadpotentially reduced against growth of bacteria as play of inhibition’s zone onNA media culture. Mostly 100% (P 3 ) of binahong leaf juice concentrations wasthe best treatment that gave inhibition zone in Staphylococcus aureus(9.72 ± 4.36 mm) and Escherichia coli (9.15 ± 4.57 mm). This could be concludedthat binahong’s leaf juice had an ability avoid growth of mastitis bacteria andit can be potentially used as herbal antibacterial in teat dipping to againstmastitis.